The Uberization of Mozambique's heroin trade - Joseph Hanlon (London School of Economics and Political Science (LSE), Department of International Development, 2018)
Mozambique is a significant heroin transit centre and the trade has increased to 40 tonnes or more per year, making it a major export which contributes up to 100 mn per year to the local economy. For 25 years the trade has been controlled by a few local trading families and tightly regulated by senior official of Frelimo, the ruling party, and has been largely ignored by the international community which wanted to see Mozambique as a model pupil. But the position is changing and Mozambique may be coming under more donor pressure. Meanwhile the global move toward the gig economy and the broader corruption of Mozambican police and civil service makes it easier to organise alternative channels, with local people hired by mobile telephone for specific tasks. Mozambique is part of a complex chain which forms the east African heroin network. Heroin goes from Afghanistan to the Makran coast of Pakistan, and is taken by dhow to northern Mozambique. There, the Mozambican traffickers take it off the dhows and move it more than 3000 km by road to Johannesburg, and from there others ship it to Europe.
Keywords: 330; Mozambique; heroin; drugs; transnational crime; smuggling; Whatsapp